Inclusive Education for Disabled— Teachers’ Reflections - Sood, Vishal; Anand, Arti (JOURNAL OF INDIAN EDUCATION, 2011)
Inclusive education is the need and demand of present day cohesive and inclusive society. The fundamental rights enshrined in our Constitution make provisions for access, equity and equality of all type of opportunities (including educational opportunities) to all persons irrespective of their class, caste, creed, religion and physical and psychological variation. This calls for the adoption of principles of imparting education to all type of children in inclusive situations. Hence, the present investigation was undertaken to study the views and perception of elementary school teachers regarding different aspects of inclusive education. The data for the present investigation were collected from 200 elementary school teachers from Kullu and Kangra districts of Himachal Pradesh with the help of self-developed ‘Scale for teachers’ attitude towards inclusive education’ and a ‘questionnaire’ for elementary school teachers. The data were analysed with the help of percentage analysis and responses to open-ended questions in the questionnaire were interpreted with the help of content analysis technique. The results revealed that majority of teachers possessed moderately favourable opinion towards different aspects of inclusive education. However, certain problems have been highlighted by the teachers that are acting as hindrances in making inclusive education, a successful venture. The suggestions have also been formulated for making inclusive education more effective in near future.